Identifying governance challenges in ecosystem services management–Conceptual considerations and comparison of global forest cases - Falk, Thomas; Spangenberg, J.H.; Siegmund-Schultze, M.; Kobbe, S.; Feike, T.; Kuebler, D.; Settele, J.; Vorlaufer, T (Elsevier, 2018)
Ecosystems around the world generate a wide range of services. Often, there are trade-offs in ecosystem service provision. Managing such trade-offs requires governance of interdependent action situations. We distinguished between (1) enhancing action situations where beneficiaries create, maintain, or improve an ESS and (2) appropriation action situations where actors subtract from a flow of ESS. We classified ESSs in order to identify focal action situations and link them to ESS governance types which are likely to strengthen sustainable ecosystem management. The classification is applied to six forest cases in Asia, Africa and Latin America. Our results confirm that ecosystem management, which more strongly supports the provision of public goods and common pool resources, is often under strong pressure to be transformed into systems that mainly provide private goods. This can be partly explained by incentive constellations in the action situations of public goods and common pool resources. Therefore, governance has to be adapted to specific ESSs. ESS governance needs to identify institutions which best fit to different ESSs and to harmonize them for all the ESSs provided by the system. Our approach helps to understand why institutions fail or succeed in maintaining ESSs.